The Improvement of Teacher's Ability in Creating Innovative Lesson Plan through Discussion with Practice - Sudibyo Sudibyo (International Research-Based Education Journal, 2020)
This study aims to describe the improving commitment and teacher's ability in creating an innovative lesson plan through practice work with feedback. The method use classroom action research in two cycles. The results are: (1) improvement of teacher's commitment in designing innovative lesson plan, with 92 percent of teachers can reach minimum score of 4-5 in widescale 1-5; and (2) improvement of teachers' ability to designing innovative lesson plan, with 92 percent of teachers are able to reach minimum score of 4-5. The strategy of practice work with feedback proves to increase the teachers' work in designing an innovative lesson plan.